Revendications morales et politiques d’une révolte. Les émeutes du Mzab en Algérie (2013-2015) - Laurence Dufresne Aubertin (L’Année du Maghreb)
From the ordinary representations of politics and local production of the feeling of injustice, this article focuses on the meaning of the riotous engagement in the Mzab, which goes beyond communitarian reading. On the basis of moral registers, the inhabitants formulate demands for the distribution of material resources and plural recognition, aimed at rectifying social and political situations deemed unequal. These representations are formulated around narratives of marginalization - ethnic, religious, economic and territorial – which attest to desires for recognition of specificities and a demand for equal rights. This tension fuels an ambivalent relationship with the political center, which reflects the demands, possibly contradictory, of a «greater» integration and autonomy.